2021
DOI: 10.1177/23814683211042010
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Electronic Clinical Decision Support Tool Into Routine Care: A Qualitative Study of Stakeholders’ Perceptions of a Post-Mastectomy Breast Reconstruction Tool

Abstract: Objective. To explore barriers and facilitators to implementing an evidence-based clinical decision support (CDS) tool (BREASTChoice) about post-mastectomy breast reconstruction into routine care. Materials and Methods. A stakeholder advisory group of cancer survivors, clinicians who discuss and/or perform breast reconstruction in women with cancer, and informatics professionals helped design and review the interview guide. Based on the Consolidated Framework for Implementation Research (CFIR), we conducted qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…57,58 After discussing relative costs of options (or more precise costs if known or included from insurance support and/or cost comparison tools 43,45,46,59 ), there are referrals that clinicians or PtDAs can suggest for members of care teams that can help patients navigate the specific direct or indirect cost implications of care (e.g., social workers, financial navigators, insurance representatives, community resources), although few currently do so. 21,48 By mentioning costs and helping patients consider those costs in the context of SDM, patients could seek support earlier to better prepare for direct and indirect costs, should they continue to choose or need expensive or Financial toxicity (burden of high costs of care) is prevalent across conditions and countries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Clinicians rarely bring up costs without prompts and training Patients want clinicians to bring up costs as part of treatment discussions, in some contexts finding clinicians trustworthy, honest, and transparent when they address costs 24 Patients often worry that if they bring up cost, it will lead to biases and lower-quality care [26][27][28] Patient decision aids and standards rarely include relative costs to compare options 53,54 When costs are discussed, they rarely include downstream direct or indirect costs (e.g., costs that build over time, relating to frequent monitoring or ongoing morbidity) 31 Making space to ask about costs supports broader care goal conversations and practical issues affecting implementation 31,32,55 Table 2 Summary of Action Items ...…”
Section: A Call To Action For Sdm and Ptda Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 After discussing relative costs of options (or more precise costs if known or included from insurance support and/or cost comparison tools 43,45,46,59 ), there are referrals that clinicians or PtDAs can suggest for members of care teams that can help patients navigate the specific direct or indirect cost implications of care (e.g., social workers, financial navigators, insurance representatives, community resources), although few currently do so. 21,48 By mentioning costs and helping patients consider those costs in the context of SDM, patients could seek support earlier to better prepare for direct and indirect costs, should they continue to choose or need expensive or Financial toxicity (burden of high costs of care) is prevalent across conditions and countries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Clinicians rarely bring up costs without prompts and training Patients want clinicians to bring up costs as part of treatment discussions, in some contexts finding clinicians trustworthy, honest, and transparent when they address costs 24 Patients often worry that if they bring up cost, it will lead to biases and lower-quality care [26][27][28] Patient decision aids and standards rarely include relative costs to compare options 53,54 When costs are discussed, they rarely include downstream direct or indirect costs (e.g., costs that build over time, relating to frequent monitoring or ongoing morbidity) 31 Making space to ask about costs supports broader care goal conversations and practical issues affecting implementation 31,32,55 Table 2 Summary of Action Items ...…”
Section: A Call To Action For Sdm and Ptda Guidelinesmentioning
confidence: 99%
“…[so] do I want to go forward with [treatment] because of the financial piece of it? It’s a big part of it.” 8 Another commented, “You know, it took about three-and-a-half years to pay off my surgeries.” 8 Although financial toxicity is often discussed in the context of cancer, it also affects patients with long-term illnesses such as hepatitis C virus, chronic kidney disease, cardiovascular disease, rheumatoid arthritis, and diabetes. 9 11 …”
mentioning
confidence: 99%
“…Details on this stakeholder engagement process and results have been published previously. 17 To address the issue of proper timing, we leveraged the EHR's ability to automatically track each discrete step in the clinical workflow. Patients received a notification through the EHR patient portal or through email if a patient was not enrolled in the patient portal.…”
Section: Recommendation 1: Engage Patient Clinician and Informatics S...mentioning
confidence: 99%
“…16 A major limitation of the original tool was that clinicians did not consistently know when patients had used it or what their risks and preferences were. 17 Clinicians did not consistently view the patient summary because of the lack of integration into their workflow in the electronic medical record. Thus, we chose to integrate BREASTChoice into the electronic medical record for clinicians and the patient portal for patients.…”
mentioning
confidence: 99%
“…In response to feedback from the earlier trial [13] and a stakeholder advisory board, preliminary work and tool adaptation included integrating photos, and improving the layout, ow of the risk page, and order of the information to ensure that they were patient-centered and relatable to users. A follow-up study evaluated factors that could impact implementation of the BREASTChoice tool according to patients, clinicians, and informatics professionals [14]. Stakeholders reported that BREASTChoice had the potential to facilitate shared decision-making, improve work ow, and enhance the e ciency of a breast reconstruction consultation.…”
Section: Introductionmentioning
confidence: 99%